Taguchi design for optimization of structural and mechanical properties of hydroxyapatite-alumina-titanium nanocomposite. Issue 8 (1st June 2019) - Ebrahimi, Mohsen; Mobasherpour, Iman; Bafrooei, Hadi Barzegar; Bidabadi, Fatemeh Shirani; Mansoorianfar, Mojtaba; Orooji, Yasin; Khataee, Alireza; Mei, Changtong; Salahi, Esmaeil; Ebadzadeh, Touradj
Abstract: The Taguchi methodology was utilized to determine the influence of three factors, namely nanostructured alumina (A) and micro-structured titanium (B) weight percents and sintering temperature (C) on the phase stability, mechanical and structural properties of hydroxyapatite (HA) composites. HA nanosized powder was synthesized via wet precipitation method. According to L9 orthogonal array, different combinations of powder mixtures were cold isostatically pressed and pressure-less sintered in a reducing atmosphere. XRD analysis confirmed the presence of HA phase and metallic Ti after sintering. Analyze of Variance (ANOVA) method was used to specify the percentage contributions of three factors. Addition of 5–10 wt% titanium contributed to increasing the decomposition of HA and the amount of open porosity by 43.07% and 55.40%, respectively and caused a decrease in the strength by 44.67%. Alumina nanoparticles consistently inhibited the grain growth but showed a negligible effect on the decomposition of HA. It also caused enhancements in the strength and toughness by 14.61 and 23.70% contributions. According to ANOVA, sintering temperature illustrated considerable effects on the properties of HA composites. It exhibited more than 56% contribution to the grain growth and decomposition of HA. Structural investigations led to a total optimum condition with a combination of 7 wt % alumina/3 wt % titanium/1150 °C.